The Oxford history of ancient Egypt - Shaw, Ian, 1961- (Oxford ; New York : Oxford University Press, 2000)
The Oxford History of Ancient Egypt uniquely covers 700,000 years of ancient Egypt, from c. 700,000 BC to AD 311. Following the story from the Egyptians' prehistoric origins to their conquest by the Persians, Greeks, and Romans, this book resurrects a fascinating society replete with remarkable historical information. It investigates such subjects as the changing nature of life and death in the Nile valley to some of the earliest masterpieces of art, architecture, and literature in the ancient world. The authors--an international team of experts working at the cutting edge of their particular fields--outline the principal sequence of political events, including detailed examinations of the three so-called 'intermediate periods' which were previously regarded as 'dark ages' and are only now beginning to be better understood. They also examine cultural and social patterns, including stylistic developments in art and literature. Addressing the issues surrounding this distinctive culture, vividly relating the rise and fall of ruling dynasties, exploring colourful personalities, and uncovering surprising facts.--
Introduction : chronologies and cultural change in Egypt / Ian Shaw -- Prehistory : from the Palaeolithic to the Badarian culture (c. 700,000-4000 BC / Stan Hendrickx and Pierre Vermeersch -- The Naqada period (c. 4000-3200 BC) / Béatrix Midant-Reynes -- The emergence of the Egyptian state (c. 3200-2686 BC) / Kathryn A. Bard -- The Old Kingdom (c. 2686-2125 BC) / Jaromir Malek -- The First Intermediate period (c. 2160-2055 BC) / Stephan Seidlmayer -- The Middle Kingdom renaissance (c. 2055-1650 BC) / Gae Callender -- The Second Intermediate period (c. 1650-1550 BC) / Janine Bourriau -- The 18th dynasty before the Amarna period (c. 1550-1352 BC) / Betsy M. Bryan -- The Amarna period and the Later New Kingdom (c. 1352-1069 BC) / Jacobus Van Dijk -- Egypt and the outside world / Ian Shaw -- The Third Intermediate period (1069-664 BC) / John Taylor -- The Late period (664-332 BC) / Alan B. Lloyd -- The Ptolemaic period (332-30 BC) / Alan B. Lloyd -- The Roman period (30 BC-AD 395) / David Peacock.
Includes bibliographical references and index.
Keywords: Egypt -- History -- To 640 A.D.